Semileptonic transition of $$\varLambda _{b}$$ Λ b baryon - Kaushal Thakkar (European Physical Journal C: Particles and Fields, 2020)
Abstract The semileptonic transition of $$\varLambda _b$$ Λ b baryon is studied using the Hypercentral constituent quark model. The six-dimensional hyperradial $$Schr\ddot{o}dinger$$ S c h r o ¨ d i n g e r equation is solved in the variational approach to get masses and wavefunctions of heavy baryons. The matrix elements of weak decay are written in terms of the overlap integrals of the baryon wave function. The Isgur-Wise function is determined to calculate exclusive semileptonic decay $$\varLambda _b$$ Λ b $$→ $$ → $$\varLambda _c$$ Λ c $$\ell $$ ℓ $${\bar{ν }}$$ ν ¯ . The calculated decay rate and the branching ratio of $$\varLambda _b$$ Λ b baryon are consistent with other theoretical predictions and with the available experimental observations.